2020
DOI: 10.1002/anie.201915262
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Strong Globular‐Protein‐Based Fibers Obtained Using a Microfluidic Spinning Technique

Abstract: Proteins used for the formation of light weight and mechanically strong biological fibers are typically composed of folded rigid and unfolded flexible units. In contrast to fibrous proteins, globular proteins are generally not regarded as a good candidate for fiber production due to their intrinsic structural defects. Thus, it is challenging to develop an efficient strategy for the construction of mechanically strong fibers using spherical proteins. Herein, we demonstrate the production of robust protein fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 45 publications
0
56
0
Order By: Relevance
“…This behavior is in agreement with the synchrotron radiation small‐angle X‐ray scattering (SR‐SAXS) analysis (Figure E), confirming the ordered alignment of the proteins in the fibers. All these results suggest that long‐range ordered internal structures can be realized by post‐stretching treatment (Figure F) …”
Section: Figurementioning
confidence: 68%
“…This behavior is in agreement with the synchrotron radiation small‐angle X‐ray scattering (SR‐SAXS) analysis (Figure E), confirming the ordered alignment of the proteins in the fibers. All these results suggest that long‐range ordered internal structures can be realized by post‐stretching treatment (Figure F) …”
Section: Figurementioning
confidence: 68%
“…The fabrication of photo‐switchable bioengineered protein‐surfactant fibers consists of two crucial components: a cationic supercharged polypeptide ( SUP ) forming the structural basis of the fiber material and an anionic sulfonated surfactant containing an azobenzene moiety ( Azo ) (Figure 1 A). The SUPs are derived from natural elastin and were expressed recombinantly in E. coli [40–44] . The high net charge of SUP s is encoded in the pentapeptide repeat unit (VPGKG) n in which the fourth position is consisting of a lysine residue (K).…”
Section: Resultsmentioning
confidence: 99%
“…TheSUPs are derived from natural elastin and were expressed recombinantly in E. coli. [40][41][42][43][44] Theh igh net charge of SUPsi se ncoded in the pentapeptide repeat unit (VPGKG) n in which the fourth position is consisting of al ysine residue (K). Regarding the SUP used for fiber fabrication, we chose K108cys that contains two cysteines at the N-and C-terminus,r espectively.T he digit of K108cys denotes the number of positive charges along the polypeptide backbone ( Figure S1-S3, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels with an open network structure can absorb a large amount of water, making them more suitable for promoting mixing and reaction [ 37 , 38 , 39 ]. Recently, a hydrogel prepared from bovine serum albumin (BSA) has attracted widespread attention because of its low cost, facile preparation, and excellent accessibility of the ligand binding [ 40 , 41 , 42 ]. It was found that BSA hydrogel microspheres prepared through the spray-drying of glutaraldehyde (GA) cross-linked BSA showed strong autofluorescence [ 43 ].…”
Section: Introductionmentioning
confidence: 99%